2011
DOI: 10.5402/2011/748939
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Disorders in South India

Abstract: Cation exchange-high performance liquid chromatography (CE-HPLC) is increasingly being used as a first line of investigation for hemoglobinopathies and thalassemias. Together with a complete blood count, the CE-HPLC is effective in categorizing hemoglobinopathies as traits, homozygous disorders and compound heterozygous disorders. We carried out a one year study in Apollo Hospitals, Chennai (Tamil Nadu, South India) during which 543 abnormal chromatogram patterns were seen. The commonest disorder we encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 4 publications
5
33
0
Order By: Relevance
“…This is comparable with other studies. [8,9,10,11] HbS trait was the second most common Hb disorder in the present study while HbE trait occupied the second position in other studies across the Indian population. [9,10] However Balgir and others have found Sickle cell anemia more common in Orissa, Eastern India.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This is comparable with other studies. [8,9,10,11] HbS trait was the second most common Hb disorder in the present study while HbE trait occupied the second position in other studies across the Indian population. [9,10] However Balgir and others have found Sickle cell anemia more common in Orissa, Eastern India.…”
Section: Discussionsupporting
confidence: 54%
“…[17] α Thalassemia and HbD were the less common Hb disorder in the present study similar to the other studies by Vani and others who reported 1.6% and 0.7% of these cases respectively. [8] The predominant feature in HbH disease is the presence of HbH ranging between 0.8% to 40% with normal or slightly reduced HbA2. [19] In the present study, HbH of 28.3% and HbA2 of 2.1% were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Rao et al [5] Singh et al [9] Patel et al [10] Alam et al [8] Chandra-Sekhar et al [11] Gupta et al [7] Mondal et al [12] Khera et al [13] HbS …”
Section: Resultsmentioning
confidence: 99%
“…Variations in the prevalence of the b S gene have been reported in various Scheduled Castes (SC) and Scheduled Tribes (ST) within different regions throughout India. There have been several previous studies on community screening in different communities for the b S gene but the number of individuals studied have been few; some studies have been hospital-based and the methodology used has not been uniform (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). While sickle cell disease is common among many different ethnic groups, high prevalence has been reported in three historically disadvantaged ethnic categories: the SC, the ST and Other Backward Class (OBC) groups in India .…”
Section: Introductionmentioning
confidence: 99%